Toxicity of agrochemical formulations - Carmichael, N. G. (Scandinavian Journal of Work, Environment & Health, 2005)
Most agrochemicals have physicochemical properties that make it impractical to apply them directly to crops and other targets. It is necessary to provide a concentrate of the active ingredient, to which formulation agents have been added to allow dilution with water for spraying. These ingredients perform several functions, including emulsifying, solubilizing, antifoaming, and the like. The properties of these materials are not intended to include pesticidal activity. However, some of these materials may have intrinsic toxicologic properties that should be taken into account in an overall evaluation of the safety of the product. In agriculture, exposure to these materials is sporadic and seasonal. The testing of the complete formulation is based on the evaluation of this risk, and it is concentrated on the evaluation of the short-term exposure to the concentrated product. Many of these substances are rather banal and are generally regarded as safe. Exceptions to this rule do exist, particularly concerning solvents; in such cases a fuller data package is necessary to perform risk assessment.
Keywords: agrochemical formulations; inert; review; risk assessment; solvent; toxicity